2009
DOI: 10.1128/iai.00671-09
|View full text |Cite
|
Sign up to set email alerts
|

Branched-Chain Amino Acids Are Required for the Survival and Virulence ofActinobacillus pleuropneumoniaein Swine

Abstract: In Actinobacillus pleuropneumoniae, which causes porcine pleuropneumonia, ilvI was identified as an in vivo-induced (ivi) gene and encodes the enzyme acetohydroxyacid synthase (AHAS) required for branchedchain amino acid (BCAA) biosynthesis. ilvI and 7 of 32 additional ivi promoters were upregulated in vitro when grown in chemically defined medium (CDM) lacking BCAA. Based on these observations, we hypothesized that BCAA would be found at limiting concentrations in pulmonary secretions and that A. pleuropneumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…BCAA biosynthesis is critical for survival and virulence of pneumococcal pathogens. A small amount of essential BCAA exists in a healthy pig lung and A. pleuropneumoniae, a respiratory pathogen causing swine pneumonia, seems to be responsible for such a low level of BCAA [6]. The ilvI mutant of A. pleuropneumoniae inhibits growth of the pathogen in respiratory swine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…BCAA biosynthesis is critical for survival and virulence of pneumococcal pathogens. A small amount of essential BCAA exists in a healthy pig lung and A. pleuropneumoniae, a respiratory pathogen causing swine pneumonia, seems to be responsible for such a low level of BCAA [6]. The ilvI mutant of A. pleuropneumoniae inhibits growth of the pathogen in respiratory swine.…”
Section: Discussionmentioning
confidence: 99%
“…The BCAA pathways are critical for the survival and virulence of pathogenic bacteria. For instance, the BCAA biosynthetic pathway of pathogenic Actinobacillus pleuropneumoniae is involved in swine pneumonia [6]. A. pleuropneumoniae ilvI mutant showed defects in BCAA synthesis, inhibited growth and reduced virulence in swine.…”
Section: Introductionmentioning
confidence: 99%
“…The BCAA biosynthesis and transport system is well studied in A. pleuropneumoniae. The presence of these amino acids is required for the survival of the bacterium and their lack is responsible for the expression of both genes for their own biosynthesis, and virulence-related genes, as demonstrated in pigs (Wagner and Mulks 2006;Subashchandrabose et al 2009). GcvB is also known to regulate the PhoQ-PhoP two-component system, which is involved in magnesium homeostasis, pathogenicity, cell envelope composition, and acid resistance in several bacterial species (Coornaert et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…While it has been shown that A. pleuropneumoniae produces PNAG-based biofilms, the role of biofilm in the pathobiology of porcine pleuropneumonia remains to be elucidated. It is clear that production of biofilms is not essential for experimental infection models that utilize the intratracheal route, since A. pleuropneumoniae ATCC 27088, a biofilm-negative strain, is highly virulent (6,27,53). However, it is possible that the infectious dose for a biofilm-positive strain is lower than that for an isogenic biofilm-negative strain or that biofilm formation might be critical for colonization and infection via an intranasal route of infection.…”
mentioning
confidence: 98%
“…A total of 25% (8/32) of the in vivo-induced genes, including hfq, were upregulated under limitation of the branched-chain amino acids (BCAAs) isoleucine, leucine, and valine in defined laboratory medium (5). Limitation of BCAAs is one of the host signals encountered by A. pleuropneumoniae in porcine lungs, and the ability to synthesize BCAAs is essential for the survival and virulence of A. pleuropneumoniae during experimental infection (6).…”
mentioning
confidence: 99%